State of exception, neoliberalism and education: the question of human dignity (Olhar de Professor, 2023)
Based on contemporary theories on the State of exception and neoliberal rationality, the present study aimed to answer the following question: do neoliberal policies for Brazilian education contribute to the ineffectiveness of the principle of human dignity? Such an investigation is urgent, especially because human dignity is the foundation of the Brazilian Republic and democratic rule of law. As specific objectives, the research conceptualized the constitutional principle of the dignity of the human person and, subsequently, related it to the context of neoliberal education policies and to the concept of the State of exception. The methodology was based on a bibliographical research of a hermeneutic and qualitative nature for the application of the theoretical framework adopted, since the study deals with investigating the study tried to investigate a political and social phenomenon. In the end, it is concluded that such rationality, allied to recent educational policies, promote a structural degradation of democracy, since it exhaust the effectiveness of one of its main foundations, the dignity of the human person.
Keywords: State of exception.; Neoliberalism.; Education.